Legislative, Rehabilitative, and Educational Approaches in Counter-Terrorism: A Theoretical and Comparative Review: Pendekatan Legislatif, Rehabilitatif, dan Pendidikan dalam Pemberantasan Terorisme: Tinjauan Teoretis dan Komparatif - Safaruddin Harefa (Indonesian Journal of Counter Terrorism and National Security, 2025)
This paper examines the integrative potential of legislative, rehabilitative, and educational strategies in Malaysia’s counter-terrorism policy, particularly within the framework of Preventing and Countering Violent Extremism (PCVE). The main problem addressed is the fragmented implementation of these three pillars, which often operate in isolation despite their complementary roles. The objective of this study is to analyze how these strategies interact, and to assess the extent to which Malaysia’s PCVE framework aligns with integrative models applied in other regions, such as South Asia and Latin America. Employing a qualitative literature-based method, the study draws from official policy documents, academic research, and comparative analysis to explore institutional strengths, implementation gaps, and strategic opportunities. The findings show that while Malaysia has developed a comprehensive legal and institutional infrastructure, coordination among state actors and involvement of civil society remain limited. The comparison reveals that inclusive governance and cross-sector collaboration significantly enhance the effectiveness of counter-terrorism efforts. The paper concludes that Malaysia’s PCVE strategy would benefit from a more interconnected approach that emphasizes transparency, participatory frameworks, and education-driven resilience. These insights offer valuable contributions to the refinement of Malaysia’s national security strategy and provide broader implications for sustainable and rights-based counter-terrorism policies globally